Controllable structure of fibrous SiO 2 –ZSM-5 support decorated with TiO 2 catalysts for enhanced photodegradation of paracetamol - Aziz, F. F. A. (Elsevier B.V., 2018)
Fibrous silica ZSM-5 (FSZ) was synthesized by a microemulsion method, and subsequent incorporation of 5 wt% of TiO 2 onto it via electrolysis in varying concentrations of supporting electrolyte tetraethylammonium perchlorate (TEAP) gave TFSZ catalysts. The results verified that the degree of desilication and dealumination, for increasing the insertion of Ti ions into the FSZ framework, was directly proportional to the concentration of TEAP. In parallel, impurity levels of Si–O–Ti bonds, defect sites and oxygen vacancies were formed and enhanced the photodegradation of paracetamol (PCT). However, excess Si–O–Ti interactions, as a consequence of a higher degree of desilication and dealumination, decreased the number of oxygen vacancies and surface defects, resulting in a higher band gap energy. The sequence towards the degradation of PCT was in the following order: 0.2-TFSZ (96%) > 0.1-TFSZ (88%) > 0.3-TFSZ (67%). The kinetics study followed the pseudo-first-order Langmuir–Hinshelwood model. The response surface methodology revealed that the initial concentration of PCT, catalyst dosage and pH were the significant factors in the degradation of PCT. The 0.2-TFSZ maintained the photocatalytic activities after five runs and able to degrade other endocrine disrupting chemicals efficiently, indicating its potential use in the wastewater treatment of those chemicals.